Fabrication, thermal and electrical properties of polyphenylene sulphide/copper composites - Goyal, R. K.; Kambale, K. R.; Nene, S. S.; Selukar, B. S.; Arbuj, Sudhir S.; Mulik, Uttam P. (Materials Chemistry and Physics, 2011)
The thermal and electrical properties of high performance poly(phenylene sulphide) (PPS) composites reinforced up to 31 vol% Cu particles were investigated to be used as materials for electronic applications. The thermal stability and char yield of the composites increased significantly. Both pre- and post- glass transition coefficient of thermal expansion (CTE) of composites decreased significantly. The microhardness was increased by more than 50% compared to pure PPS matrix. Microhardness and CTE of composites correlated well with the rule of mixtures. A percolation threshold about 6 vol% Cu was obtained. The electrical conductivity was increased by about eight orders of magnitude for 18 vol% composite. Dielectric constant and dissipation factor of composites at 1 MHz was increased by about 6-fold and 70-fold compared to matrix, respectively. They decreased gradually with increasing frequency up to 1 MHz and thereafter, there was insignificant change. The scanning electron microscope showed almost uniform distribution of Cu particles in the matrix. Owing to better dimensional stability and good electrical properties, these composites are very promising for electronic applications. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Dielectric property; Electrical conductivity; hardness; Thermal expansion

PEEK/SiO2 composites with high thermal stability for electronic applications - Goyal, R. K.; Rokade, K. A.; Kapadia, A. S.; Selukar, B. S.; Garnaik, Baijayantimala (Electronic Materials Letters, 2013)
Thermal and mechanical properties of new high performance polymer matrix composites based on poly(etheretherketone) (PEEK) as matrix and crystalline-silica (SiO2) as reinforcement were discussed for application in electronic packaging substrates or printed circuit boards. The content of SiO2 was varied between 0 and 50 wt. %. Scanning electron microscopy showed uniform dispersion of SiO2 particles in the matrix. Thermogravimetry analysis showed significant increase in thermal stability and char yield with increase in SiO2 content in the matrix. Differential scanning calorimetry showed that SiO2 had a heterogeneous nucleating effect on PEEK, leading to an increase in peak temperature of crystallization and onset crystallization temperature of the composites compared to a pure matrix. The microhardness increased approximately 42%. A modified rule of mixtures with a strengthening efficiency factor equal to 0.06 fit the data nicely. The results show that the prepared PEEK/SiO2 composites may have potential applications in electronics.
Keywords: hardness; PEEK; polymer matrix composites; Thermal properties

Synthesis of biomass waste derived activated carbon-NBR composites for automobile application - Jadhav, A.; Mohanraj, G.T.; Gokarn, A.; Mayadevi, S. (Chemistry and Chemical Technology, 2018)
This paper reports on usability of activated carbon obtained from areca nut shell, coconut shell, and coconut leaves as a filler to prepare NBR based composite for automobile based application. The carbon was activated by phosphoric acid (H3PO4) as dehydrating agent. The stoichiometric ratio of biomass and phosphoric acid was found to be 3:1 for the batch size of 300 g. As compared to commercially available carbon filler, the activated carbon derived from biomass waste responded better to the petrol swelling test. Among three biomass waste sources, namely, areca nut shell, coconut shell, and coconut leaves, activated carbon derived from coconut shell was appeared to be the best for percent swelling and percent deviation in hardness. The results obtained are confirmed by proximate analysis.
Keywords: activated carbon; composites; hardness; NBR; Phosphoric acid

Role of Li+ and Fe3+ in modified ZnO: Structural, vibrational, opto-electronic, mechanical and magnetic properties - Bajpai, G.; Moirangthem, I.; Sarkar, S.; Barman, S. R.; Vinod, C. P.; Bajpai, S.; Riyajuddin, S.; Ghosh, K.; Basaula, D. R.; Khan, M.; Liu, S. -W.; Biring, S.; et al. (Ceramics International, 2019)
When Fe is doped in ZnO, a situation of charge imbalance is created due to the higher charge of Fe3+. A charge balance may be obtained by co-doping Li+0.5Fe3+0.5 combinations. A solid solution of Zn1-x(Fe0.5Li0.5)xO (0 ≤ x ≤ 0.03125) is synthesized with this viewpoint. The crystallites belong to a wurtzite P63mc space group, with lattice parameters a, b and c increasing nominally for x = 0.0156 and thereafter remaining invariant. The size varies in the range ~ 60–142 nm. Interstitials of Li and Zn ions are formed. Along with Fe3+ substitution these defects are reasons for O interstitials. These oxygen interstitials increase the red emission while reduction of oxygen vacancies reduces the green emission. These point defects create structural distortion and strain which can generate Zn vacancies. Bandgap reduces due to shallow defects. Mid-bandgap states due to oxygen interstitials and Fe 3d-O 2p hybridization result in NIR emission. On the other hand the crystal surface deforms due to Li addition which hardens the materials. A weak ferromagnetism appears at very low temperature which is enhanced by Li+ addition. Long range exchange mechanism between Fe3+ ions appears in the samples, mediated by magnetic polarons due to point defects.
Keywords: hardness; NIR emission; Shallow and deep level defects; Weak ferromagnetism; ZnO